Epidermal Growth Factor Receptor (EGFR) and Vascular Endothelial Growth Factor (VEGF) expression in Sinonasal Inverted Papillomas - Mario Bilic; Ena Klaric; Lana Kovac-Bilic; Selma Hodzic-Redzic; Sven Seiwerth (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
The aim of this study was to evaluate the expression of Epidermal Growth Factor Receptor (EGFR) and Vascular Endothelial Growth Factor (VEGF) in patients with primary inverted papilloma (IP), recurrence of IP and carcinoma based on IP. The study was performed on an archived material of the 52 patients that were surgically treated because of the primary IP, recurrent IP and carcinoma that developed on the ground of IP on the Tertiary care University Center in the period of 18 years. The expression of the EGFR and VEGF were measured by an immunohistochemistry method using commercially available antibodies. There is a significant difference in expression of EGFR comparing primary IP to recurrence and squamous cell carcinoma (SCC) in the region of squamous and dysplastic epithelium, and also in the region of metaplastic epithelium between primary IP and carcinoma. There is a significant difference in expression of VEGF compared primary IP to recurrence and SCC in the region of the squamous and dysplastic epithelium. The recurrence of IP presents step in tumour's transformation between benign lesion and carcinoma.